âPERENCANAAN PROMOSI JABATAN STRUKTURALâ (Studi Kasus di Kabupaten Polewali Mandar) - , M. Junaid AR, SE, Prof. Dr. Warsito Utomo ([Yogyakarta] : Universitas Gadjah Mada, 2012)
After the enactment of the regional autonomy, the regions have the power to manage personnel administration including in determining the promotion ofstructural position. Inthe regency of PolewaliMandar, the process of structural job promotion was performed administratively by BKDD (the Agency of Personnel and Regional Training) and Baperjakat. However the process of recruitment and promotion performed had been indicated that it had not fully referred to the provisions of Act No. 34 of 1999 on the points of personnel, demanding that the process should be performed in professional way. The available decision-making process is still influenced by political decisions. The purpose of this research is to describe and analyze the planning of positionpromotion and to understand the factors affecting the planning of position promotion in PolewaliMandar. The descriptive qualitative method with Phenomenology approach was used in this research. Thedetermination of informant in this research was performed intentionally (purposive sampling). Data collection techniques used is interviews and library studies. Interview data were used to obtain primary data while the documentdata wereused to obtain secondary ones. Data analyses wereconducted with the step sequences of reduction, presentation and conclusion of data. The analysis were performed by means of collecting and sortingthe data according to their relevancy, then it were described, to respond to the formulation of problems, and (were) concluded. The results showed that the planning of structural position promotion had been conducted through the sequence of steps, i.e. firstly, the analysis and the building of work design were conducted. The analysis of work provided information for the organization they got from the description of duties and also for the assessment of work. The process of determining the job difficulty level.Secondly, there are vacancies and the information of opportunities. In an organization there must be available information on the opportunities which will be occupiedby the prospective fulfilling the administrative qualification to occupy certain administration post. Factors influencing the planning of structural post promotion in PolewaliMandar regency among others are: The first, the factor of honesty. The assessment of honesty was performed administratively by using theavailable portfolio of Implementation Assessment list Documents(DP3), which is an official document of the result of assessment by supervisor toward promoting candidate.But, it was alleged that the value of score written in the DP3 document was not completely authentic in its filling process. The second, the factor of discipline inthe PolewaliMandar regency. The discipline factor as one of those influencing factors, inthe appointment of structural officials. Administrative reason for assessing this disciplinary (in addition to DP3) is the notes of presence. The third, the factor of cooperation. Cooperation factor was applied by Baparjagat and BKDD in considering someone to occupy structural position. This cooperation was considered being very important, given that structural officers would manage an organization. The administrative reason was that DP3 coupled with special verification for the Echelon III upwards.The fourth,the factor of job performance. This job performance assessment was indeed a factor that into consideration by Baparjakat or BKDD. Administrative reason used was DP3 containing one point about the value of job performance prospective. The Fifth, the factor of know-how (skills). Skills was used by Baperjakat and BKDD in considering someone who is to occupy structural position.The sixth, the factor of education level. The education level was an absolute requirement for promotion. It has been set out clearly on the level of education or training for new position.The seventh, the factor of experience. The experience factor here was made reference in the appointment of a person in to structural position. Based on the results of research, it was shown that much of administrative and selection processes performed by BKDD and Baperjakat later were useless because of the authority of regent which was much influenced by practical politics.